Cigarette smoking and risk of premature stroke in men and women. Issue 6538 (5th July 1986) - Bonita, R; Scragg, R; Stewart, A; Jackson, R; Beaglehole, R
Abstract : A case-control study was carried out of the relation between cigarette smoking and hypertension and stroke. A total of 132 cases of stroke (79 in men, 53 in women) identified as a part of a population based register were compared with 1586 controls (1017 men, 569 women) from a survey of cardiovascular risk factors conducted in the same population. Cigarette smokers had a threefold increase in the risk of stroke compared with current non-smokers. This association remained significant after adjusting for hypertension. Those who both smoked and had hypertension had an increased risk of stroke of almost 20-fold compared with those who neither smoked nor had hypertension. Overall, in this population roughly 37% of stroke events may be attributed to cigarette smoking and 36% to hypertension.